Total leadership be a better leader, have a richer life - Friedman, Stewart D. (Boston Harvard Business Review Press, 2014)
Now in paperback, this national bestseller proves more than ever, your success as a leader isn't just about being great at business. You must be a great person, performing well in all domains of your life-including work, home, community, and your private self. The good news is that, contrary to conventional wisdom about "balance," you don't have to assume that these domains compete in a zero-sum game. Total Leadership is a game-changing blueprint for how to perform well as a leader not by trading off one domain for another, but by finding mutual value among all four. Stew Friedman shows you how to achieve these "four-way wins" as a leader who can be real, be whole, and be innovative. With engaging examples and clear instruction, Friedman provides more than thirty hands-on tools for using these proven principles to produce stronger business results, find clearer purpose in what you do, feel more connected to the people who matter most, and generate sustainable change. Total Leadership is a unique resource that shows how to win in all domains of life
Includes bibliographical references and index.
Keywords: Leadership--Psychological aspects